NATIONAL EDUCATION IN FUNCTION OF DEVELOPMENT OF NATIONAL IDENTITY: THE CONTRIBUTION OF MUSIC PEDAGOGY (Heritage, 2023)
The work starts from the question of national interests and values, as well as from the importance of developing national identity for the individual and the society. Considering that national identity, the sense of belonging to the community and togetherness develops from an early age, the importance of national education in that process and its contribution to the affirmation of national values is pointed out, with special reference to the fact that a stronger sense of national identity also contributes to a higher degree of respect for other nations and developing multicultural values and interests. Besides emphasizing the importance of national education expressed in the ideas and conclusions of pedagogues and sociologists, the place of national education in the legal legislation is considered, through which educational policy is implemented, respectively, the focus of education in Serbia on the development of national identity. In that sense, areas that contain fundamental knowledge for the development of national identity are highlighted, with special reference to the contribution of content from the field of musical culture and education. Although a significant resource for developing national identity is recognized in the theoretical framework of national education, the question of strategy and methodology for developing teachers’ competence for linking and balancing theoretically based knowledge into reflective practice arises. Through the analysis of works from music pedagogy, traditional folk and spiritual music were recognized as contents that contribute to the achievement of the tasks of national education, while a very small number of works included consideration of the representation and importance of patriotic songs, Serbian artistic music, as well as traditional music of other nations, in the teaching of music culture. It is therefore necessary to encourage music pedagogues as well as teachers of other subject areas to further pedagogical-methodological research and more studious design and realisation of teaching musical culture in order to achieve the tasks of national education more successfully. As a conclusion, it is emphasized that national interests are not fixed through tradition, and that they are determined by interests, needs and the current constellation in society, which is dependent on the principles of general humanist values, while respecting the specifics of ethical communities and identities.
Keywords: National education, national identity, educational system, culture, language, history, music